2008
DOI: 10.1515/epoly.2008.8.1.1937
|View full text |Cite
|
Sign up to set email alerts
|

Residual stresses determination in injection molded virgin and recycled HDPE blends: mechanical properties and morphology

Abstract: An experimental study of residual thermal stresses has been carried out in injection molded virgin and recycled high density polyethylene (HDPE) blends. Effects of blend concentrations on residual stresses were investigated under different injection conditions such as melt temperature, mold temperature and cooling time. Layer removal technique was used for measuring residual stresses. In order to determine the relation between the residual stresses and material characteristic of HDPE blends, mechanical and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Similarly, several authors who investigated the effect of HDPE reprocessing on degree of crystallinity [6,24,26,27], did not observe any significant change on crystallinity throughout 10 reprocessing cycles. This is in line with our findings from the first 20 extrusion cycles.…”
Section: Thermal Properties and Crystallinitymentioning
confidence: 79%
See 1 more Smart Citation
“…Similarly, several authors who investigated the effect of HDPE reprocessing on degree of crystallinity [6,24,26,27], did not observe any significant change on crystallinity throughout 10 reprocessing cycles. This is in line with our findings from the first 20 extrusion cycles.…”
Section: Thermal Properties and Crystallinitymentioning
confidence: 79%
“…increasing of MFI with number of reprocessing cycles [6,26], decreasing [20,23,27,28], or they did not observe significant change [21,24,28]. Many authors concluded that intensity of MFI change can be related to the content of stabilizers [6,23,28].…”
Section: Melt Flow Indexmentioning
confidence: 99%
“…Altan et al 23 noted high residual stresses in HDPE flat plates injection molded at low T mold , which can account for the reduced impact strength. Guevara‐Morales and Figueroa‐López 24 explain that such stresses, which influence the properties of injection molded parts, are mainly associated with melt shearing during the filling and packing stages of injection molding, as well as with the different cooling rates between the skin and core of the molded part.…”
Section: Resultsmentioning
confidence: 99%
“…When samples are heated again, residual stresses are released, leading to dimensional changes on the sample [50,51]. According to literature, higher residual stresses are stored in a recycled polymer than in raw materials [52]. Thus, higher stresses will be released at higher temperatures for recycled material when recycling PP, changes related to polymer structure are induced.…”
Section: Resultsmentioning
confidence: 99%